Performance Assessment of Paving Blocks with Tannery Sludge as a Partial Cement Replacement - Zhafirah, Athaya; Mulyana, Subhan (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2026)
The construction industry faces increasing pressure to adopt more sustainable practices, particularly in reducing the environmental impact of cement production, which is responsible for significant CO₂ emissions and the depletion of natural resources. One promising strategy is to partially replace cement with industrial waste materials that possess cementitious properties. This study examines the potential of tannery sludge, a hazardous byproduct of the leather tanning process, as a partial substitute for cement in the manufacturing of paving blocks. The sludge contains valuable oxides such as CaO, Al₂O₃, and Fe₂O₃, which can contribute to the binding characteristics required in concrete applications. An experimental approach was conducted to evaluate the performance of paving blocks containing 0%, 1%, 3%, and 5% tannery sludge by weight of cement. Tests included compressive strength, wear resistance, water absorption, resistance to sodium sulfate, and chemical composition analysis using X-ray fluorescence (XRF). The results revealed that all sludge-containing mixtures maintained compressive strength values exceeding the minimum threshold for class B paving blocks, making them suitable for moderate-load applications such as parking areas and pedestrian pathways. Wear resistance results placed all specimens in class A, indicating high surface durability. However, increased water absorption was observed with higher sludge content, potentially due to the porous nature of the sludge. The sodium sulfate resistance test highlighted the need for further enhancement, as weight fluctuations indicated vulnerability in chemically aggressive environments. XRF analysis confirmed the compatibility of the sludge composition with cement standards. In conclusion, tannery sludge demonstrates technical feasibility as a sustainable alternative to cement in the production of paving blocks. Its use offers environmental and economic advantages, though further research is needed to optimize performance and ensure long-term durability under various conditions.